Associations between personality and distress tolerance among trauma-exposed young adults. (1st January 2018) - Chowdhury, Nadia; Kevorkian, Salpi; Hawn, Sage E.; Amstadter, Ananda B.; Dick, Danielle; Kendler, Kenneth S.; Berenz, Erin C.
Abstract: Low distress tolerance (DT) is related to negative mental health outcomes, particularly among trauma-exposed populations, who are at greater risk for mental health problems. However, little is known about potential etiological factors underlying the development of perceived (i.e., self-report) or behaviorally assessed DT. The present study examined associations between Big Five personality factors (i.e., openness, conscientiousness, extraversion, agreeableness, and neuroticism) and multiple measures of DT. Participants were 440 college students (71.4% women) endorsing a history of one or more potentially traumatic events. Participants completed the abbreviated Big Five Inventory (BFI), Distress Tolerance Scale (DTS), Discomfort Intolerance Scale (DIS), breath-holding task, and Paced Auditory Serial Addition Test (PASAT). Results of a series of hierarchical linear regressions indicated that higher levels of neuroticism and lower levels of conscientiousness were significantly associated with lower DTS scores, but no other DT measures. Greater extraversion was significantly associated with greater DT on the DIS and the PASAT. Lower levels of openness were associated with lower DT on the breath-holding task. Individual differences in normal personality traits account for significant variation in multiple measures of DT and may provide insight into the etiology of various forms of DT. Highlights: Studied associations between personality factors and distress tolerance measures High neuroticism was associated with lower self-reported distress tolerance. High extraversion was associated with greater self-reported DT. High extraversion was associated with greater behavioral DT. Low openness was associated with lower behavioral physical distress tolerance.